Nonlocal Problem Multipoint in Time for the Evolutionary Equations with Pseudo-Bessel Operators with Variable Symbols - Horodets’kyi, V. V.; Martynyuk, O. V. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We study the properties of the fundamental solution of a nonlocal problem multipoint in time for the evolutionary equations with pseudo-Bessel operators constructed on variable symbols. The solvability of this problem is proved in the class of bounded continuous functions even on ℝ. The integral representation of solutions is established.